Peak torque and muscle balance in the knees of young U-15 and U-17 soccer athletes playing various tactical positions - Chiamonti Bona, C.; Tourinho Filho, H.; Izquierdo, M.; Pires Ferraz, R. M.; Marques, M. C. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: Soccer is a sport that is practiced worldwide and has been investigated in its various aspects, particularly muscle strength, which is an essential motor skill for sports performance. The objective of this study was to investigate the peak torque and muscle balance on the knee extensor and flexor of young soccer players in the tactical positions of goalkeeper, defender, full back, midfielder, defensive midfielder and striker, as well as to determine which field position has the highest peak torque.